Additional Issues on Screening, Prevention, and Treatment of Abdominal Aortic Aneurysms. (November 2013) - Paraskevas, Kosmas I.; Mikhailidis, Dimitri P.; Giannoukas, Athanasios D.
The prevalence of abdominal aortic aneurysms (AAAs) and AAA-related deaths are steadily declining in some countries as a result of the reduction in smoking rates. It was thus suggested that screening programs that do not target high-risk populations are likely to have very low AAA detection rates. However, this may not apply to other countries that do not exhibit similar reductions in smoking rates. It was assumed that by using the U.S. Preventive Services Task Force screening criteria (men 65-75 years with smoking history) less than 30% of AAAs would be captured. A more extensive scoring system that includes additional risk factors such as the presence of carotid artery or peripheral arterial disease, obesity, hypertension, and so on, may identify almost 90% of AAAs. This article discusses this and other issues on screening, prevention, and treatment of AAAs.